A Pragmatics Analysis of Deixis in Surah Al Baqarah Translated By Abdullah Yusuf Ali - Azzahra, Irah Khoiriyah (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2019)
This is a descriptive qualitative research that explores about non-person deixis words in surah Al-Baqarah translated by Abdullah Yusuf Ali, which concern in context reference meaning of pragmatics analysis. The data of this research was taken from 222 verses that consist of non-person deixis. The technique of collecting data is document analysis that uses pragmatics analysis approach. The technique of analyzing data is by managing, reading the script, classifying the data, describing, and interpreting. Then checklist for instrument was built of Levinson?s theory. The result of this research presents that 1) there are four types of non-person deixis used in surah Al-Baqarah translated by Abdullah Yusuf Ali namely place deixis, time deixis, social deixis, and discourse deixis. 2) There are 452 references of non-person deixis used in surah Al-Baqarah translated by Abdullah Yusuf Ali (the detail in chapter IV of this research). 3) There are context reference meaning in every deictic word in surah Al-Baqarah translated by Abdullah Yusuf Ali that analyzed. So that the readers should have deep understanding about the representation of pragmatics especially the non-person deixis to analyze the context reference meaning in Al-Qur?an English translation.Keywords: Pragmatics, Deixis, Al-Qur?an English Translation